Sosialisasi Strategi Dokumentasi Koreografi Tari Guel Berbasis Edukasi Digital - Soufyan, Dara Angreka; Risnafitri, Hafizhah; Syahrani, Rizky Amalia; Airiansyah, Fitra; Aliya, Rahma; Jilantahani; Nasuwa, Nurna Mila (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Guel Dance, a traditional art of the Gayo community in Aceh Tengah, embodies moral, spiritual, and social values through symbolic movements. In recent decades, the number of practitioners has declined, and the oral transmission process has led to the gradual loss of movement authenticity. The Depik Art Dance and Music Studio in Takengon continues to preserve this heritage but faces limitations in digital documentation and the absence of structured educational media. This community service activity aimed to enhance participants’ understanding, technical ability, and awareness of digital choreography documentation as a strategy for cultural preservation. The program was conducted on October 21-22, 2025, at the Depik Art Studio in Takengon, involving 23 community members. The implementation method combined preparation, socialization, practical training, and evaluation. Participants learned techniques for video recording, choreography metadata organization, and basic editing to produce educational dance videos. Evaluation through pre-test and post-test instruments measured the improvement in comprehension and technical competence. The results indicated an average knowledge increase of 49%, reflected in improved understanding of digital preservation and recording methods. Participants successfully produced three short educational documentaries and established a small internal documentation team. The activity also strengthened collective pride and collaboration within the Gayo artistic community. In conclusion, this program demonstrated that participatory and contextual digital training effectively supports cultural sustainability. The model offers a replicable framework for empowering local communities to preserve traditional performing arts through accessible digital archiving practices.